2003
DOI: 10.1002/ajmg.a.20017
|View full text |Cite
|
Sign up to set email alerts
|

Paternal origin of der(X)t(X;6) in a girl with trisomy 6p and unbalanced t(6;10) mosaicism in her mother

Abstract: We present a case of trisomy for the whole short arm of chromosome 6 in a 3-year-old girl with moderate mental retardation, mild facial dysmorphism, short stature, failure to thrive, and no abnormalities of the visceral organs. Cytogenetic and fluorescence in situ hybridization (FISH) analysis revealed a 46, X, der(X)t(X;6)(q22; p11.1) karyotype. The derived X was late replicating with variable spreading of X chromosome inactivation onto the translocated 6p. A normal karyotype was observed in the father, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In the literature, a number of reports have been documented on balanced and unbalanced translocation in different age groups between chromosome 6 and 10 and involving many other autosomes or sex chromosomes [610]. Generally, the detection of unbalanced type of translocation in children with facial dysmorphism, mental retardation, and growth retardation led to retrospective detection of balanced translocations in their parents.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a number of reports have been documented on balanced and unbalanced translocation in different age groups between chromosome 6 and 10 and involving many other autosomes or sex chromosomes [610]. Generally, the detection of unbalanced type of translocation in children with facial dysmorphism, mental retardation, and growth retardation led to retrospective detection of balanced translocations in their parents.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution depends on when during development the aberrant cell line occurred and the proliferation advantage or disadvantage of the aberrant cell line in different tissues. In most cases with low-level mosaicism for a balanced or unbalanced reciprocal translocation, the error is an early mitotic event that occurred after fertilization with two normal gametes and may be the consequence of somatic pairing and mitotic crossing over (12). In our case, a dicentric chromosome was formed along with an acentric fragment that was most probably lost during subsequent cell divisions.…”
mentioning
confidence: 68%
“…Mosaicism for balanced or unbalanced structural aberrations in man is extremely a rare phenomenon [Kleczkowska et al, 1990] or may be under‐diagnosed. The mechanism, prevalence, and clinical significance of this type of chromosomal anomaly are not well known [Farrell, 1991; Petkovic et al, 2003]. Balanced reciprocal translocation mosaicism has been reported in only 23 cases to our knowledge [Stenchever et al, 1977; Sciorra et al, 1985; Cantu and Ruiz, 1986; Fryns and Kleczkowska, 1986; Saura et al, 1987; Castle and Bernstein, 1988; Kleczkowska et al, 1990; Farrell, 1991; Sciorra et al, 1992; Aughton et al, 1993; Gardner et al, 1994; Opheim et al, 1995; Leegte et al, 1998; Vargas and Fernandez‐Novoa, 2001].…”
Section: To the Editormentioning
confidence: 99%
“…Mosaicism for a structural aberration is considered a rare phenomenon in the human population [Kleczkowska et al, 1990] and has never been reported in a cryptic state before. Its prevalence is unknown since low level mosaicism is easily missed [Petkovic et al, 2003]. Indeed the detection of mosaicism depends on the percentage and distribution of abnormal cells, number of cell count, type of the rearrangement, banding resolution [Sciorra et al, 1985] and especially the size of the imbalance.…”
Section: To the Editormentioning
confidence: 99%